Can an Ideal Library Guarantee High Elementary School Students' Interest in Reading? - Martesya, Anggi; Abduh, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Reading is a very important activity because it is used to disseminate information for learning. This is due to access to information and knowledge related to reading. This research aims to explore reading interest and the factors that influence reading interest in private elementary schools in Surakarta. This research uses a qualitative approach with a case study method. The informant selection technique in this research used several data collection techniques, namely observation, interviews, and documentation. The results of this research indicate that interest in reading in Surakarta private elementary schools is relatively low. Due to students' lack of reading ability, reading must be ordered by the teacher. Students often play during recess. The influencing factors are internal and external factors. Internal factors are factors that come from oneself, while external factors are from outside, such as the family environment, peers, gadgets, and libraries that are far from the classroom. In conclusion, the low interest in reading among Surakarta Private Elementary School students is influenced by several factors.